The effect of teacher‐led interventions on social and emotional behaviour in primary school children: a systematic review. (15th January 2013) - Whear, R.; Thompson‐Coon, J.; Boddy, K.; Ford, T.; Racey, D.; Stein, K.
<x xml:space="preserve">Abstract</x> The purpose of this article is to clarify the role of teacher training initiatives aimed at improving social, emotional and behavioural outcomes of primary school aged children through improved classroom management. Systematic searches were conducted using a range of electronic databases from inception up to September 2011. Included studies were controlled trials that described training provided to teachers in classroom management techniques designed to improve primary school children's behavioural and social outcomes. Study selection and appraisal of quality were carried out by two researchers and a narrative synthesis was carried out. A total of 14 studies were included involving 8 interventions. Results show that statistically significant effects are limited, with only 20 outcomes showing significant effects in the desired direction. Effect sizes ranged from g = −0.17 (95%CI: −0.32, −0.02) to g = 1.88 (95%CI: 0.55, 3.21). Overall, the programmes indicate an improvement in some outcomes of interest. However, further research into the implementation and comparative effectiveness of such programmes is needed before implications for educational policy and practice can be established.